2019
DOI: 10.1002/lt.25432
|View full text |Cite
|
Sign up to set email alerts
|

Body Image in Liver Transplantation Recipients

Abstract: Body image (BI) concerns have been reported to play a significant role in the psychological adaptation after organ transplantation. There is a paucity of data about BI beliefs in liver transplant recipients. We report the results of a cross‐sectional study of 177 liver transplant recipients for whom we assessed BI, anxiety, depression, and quality of life (QOL) using validated instruments. Our results indicate that higher BI concerns correlated with higher levels of anxiety and depression. BI concerns were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…(Yıldız, 2021). It has been reported that psychosocial problems are observed in individuals after transplantation, and there are many studies showing that these problems reduce the quality of life of LT recipients, and if not treated, may lead to problems progressing to rejection of the transplant (Calia et al, 2011; Dobbels et al, 2008; Miller et al, 2013; Rice et al, 2013; Zimbrean et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Yıldız, 2021). It has been reported that psychosocial problems are observed in individuals after transplantation, and there are many studies showing that these problems reduce the quality of life of LT recipients, and if not treated, may lead to problems progressing to rejection of the transplant (Calia et al, 2011; Dobbels et al, 2008; Miller et al, 2013; Rice et al, 2013; Zimbrean et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been shown to affect patients with terminal cardiothoracic disease significantly more when compared with patients suffering from hepatic failure (35). Negative body image, which we observed to be the most pronounced in patients evaluated for HTx, has been correlated with anxiety and depression, suggestive of a role in the setting of organ transplantation (15,36). Lack of perceived social support has been correlated with increased occurrence of depression and reduced quality of life in lung transplant patients (34).…”
Section: Discussionmentioning
confidence: 80%
“…The scores can range from 0 to 21 and can be interpreted dimensionally as well as categorically. Established cutoffs are minimal (<5), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21). In our sample, the reliability was Cronbach α = .88.…”
Section: Questionnairesmentioning
confidence: 73%
See 1 more Smart Citation
“…( 33 ) A cross‐sectional survey study of 61 liver transplant recipients found significant associations of negative self‐perceived body image with self‐reported sedentary physical activity and low QOL. ( 34 ) With respect to liver disease etiology, QOL was lowest for recipients transplanted for HCV and alcoholic liver disease. ( 32 )…”
Section: Physical Activity and Qol After Liver Transplantationmentioning
confidence: 99%